Review of Hilary Poriss. 2009. Changing the Score: Arias, Prima Donnas, and the Authority of Performance. Oxford: Oxford University Press - Cairns, Elliott S. (Current Musicology, 2011)
Readers may recall the 1998 production of Mozart's Le nozze di Figaro at the Metropolitan Opera in which mezzo-soprano Cecilia Bartoli, to much criticism, sang two arias in place of the two traditionally sung by her character, Susanna. Despite the fact that Mozart also composed these two substitute arias and despite the fact that he also composed them for Le nozze di Figaro (albeit after the original 1786 production in Vienna), Bartoli was largely lambasted by critics and audience members alike. It is fitting that Hilary Poriss would cite this example in her concluding remarks for Changing the Score: Arias, Prima Donnas, and the Authority of Performance, for although not ubiquitous, the practice of aria substitution was, at one point, not uncommon. Unfortunately for Bartoli, the practice is no longer in vogue: modern audiences by and large desire a musical experience as close to the "original" as possible, and this cannot possibly be furnished by allowing the "egocentric" whims of the diva to undermine the authority of the composer.